Empowered Learners in a Digital Age: The Critical Nexus of Engagement, Agency, Interest, and Motivation - Wahyuni, Naning Tri; Ariyanto, Gunawan (Muslim Education Review, 2024)
Integrating ICT into teaching and learning is critical to raising students’ engagement. As engagement is vital for productive learning, understanding its relevant aspects is eminently important. This paper reports the learning experience of Indonesian students who enrolled in three university courses taught in English (Academic English, Philosophy of Education, and Scientific Paper Writing). The study captured the students’ digital e-learning activities, driven by their interest-related activities and study motivation. How they navigated their way in using information and communication technology (ICT) to help with their course learning was examined. The connection between students’ agency, interest, motivation, and engagement was analyzed. The findings highlighted how the technology strengthened the nexus between agency, interest, motivation and engagement. Students’ interest in ICT uses and activity preferences motivated their learning and promoted their engagement. The students’ agency helped control their effort and perseverance, which enabled lost lasting engagement. Motivated learners with interest showed more developed agency. They exhibited determined goals, self-directed learning, and resoluteness in responding to their surroundings, including access and knowledge of technology use, aligning with their preferred ways of learning and objectives. Pedagogic implementation recommends flexible ways to accommodate students’ interests in ICT use to maintain their motivation, as both are reciprocally connected with their developed agency and engagement.